ALAT BUKTI KETERANGAN AHLI HUKUM PIDANA DALAM PROSES PEMERIKSAAN PERKARA PIDANA - Benget Hasudungan Simatupang (Ensiklopedia Social Review, 2020)
In the process of examining criminal cases such as corruption cases, the existence of a criminal law expert’s statement makes pro and contra, so that is very necessary to do a comprehensive research in the existence of expert criminal law statements. For this reason, the authors are interested in discussing the existence of statement of criminal law experts as one of the evidence in a criminal case. The problem in this research is what are the qualifications of a person to be able to ask for expert criminal law statement to be used as evidence in the trial of a criminal case. This research is a normative juridical legal research with norms approach method and case approach. The results of this research are the qualifications of someone who can provide expert criminal law statement as evidence in the trial of a criminal case is someone who has special expertise regarding knowledge and experience in the field of criminal law. The Criminal Procedure Code (KUHAP) does not provide a limitation on experts and only mentions a person who has special expertise, so that a criminal law expert can be categorized as an expert and the information given can be one of the evidence in court.